Degradation of Rh B and glycerol using contact glow discharge electrolysis (CGDE) - Rao, Yuhan (Nanyang Technological University, 2020)
In modern society, there is an increasing tendency of requirement for pursuing higher aes-thetic abilities. For example, dyeing and chemicals are one of the main perspectives in the creation of industrial pollution. As such, many different chemical methods have been devel-oped to get rid of the pollution through degradation of organic molecules. However, these methods have been still encountering the limit in low efficient process and complex proce-dures. It is still challenging to discover an approach to the improvement of degradation rate of the polluted organic contents.